Molten iron at extreme conditions reveals compositional inhomogeneity in Earth’s lower outer core - Bo Gan; Jun Li; Heli Ma; Long Hao; Zhipeng Gao; Xiang Wu; Qiang Wu; Youjun Zhang (Proceedings of the National Academy of Sciences, 2026)
The thermodynamic properties of molten iron under Earth’s outer core conditions are fundamental to understanding the core’s structure, composition, and dynamics. However, experimental constraints under such extreme conditions remain scarce. Shock compression experiments can provide a viable means of reproducing the relevant thermodynamic regime of the outer core. Here, we report precise shock temperature measurements of molten iron up to ~364 GPa, approaching pressures at the core’s center. By integrating these results with existing measurements of density and sound velocity in shock-compressed iron, we determine the thermal equation of state and compressional wave velocity ( V P ) of molten iron throughout outer core conditions. Compared with pure molten iron, Earth’s outer core exhibits a depth-increasing density deficit and a depth-decreasing V P excess, reaching ~9.0% and ~1.3% at the inner-core boundary, respectively. Notably, the density deficit flattens while the V P excess steepens within the lowermost ~280 km of the outer core. These trends reveal a heterogeneous basal outer core, comprising a partially crystallized F -layer overlain by a gradient in light-element concentration. Our findings provide direct experimental constraints on the thermodynamic behavior of molten iron under outer core conditions, offering insights into the compositional stratification, thermal evolution, and long-term sustainability of the geodynamo.